1995
DOI: 10.1021/ma00109a029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Supramolecular Tubular Structure in Oriented Fibers of a Poly(methacrylate) with Tapered Side Groups

Abstract: X-ray methods have been used to investigate the changes in structure with temperature for the supramolecular structure formed by a poly(methacry1ate) with tapered side chains. The polymer is poly[2-[2-[2-[2-(methacryloyloxy)ethoxylethoxylethoxyle~yl 3,4,5-tris[[p-(dodecyloxy)benzylloxylbenzoate]. Oriented fibers drawn from the columnar hexagonal (&J liquid crystalline phase at -60 "C adopt an ordered structure at room temperature, in which ordered cylindrical moieties are packed on a hexagonal lattice with a x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 1 publication
5
74
0
Order By: Relevance
“…This effect manifests itself in the signif icant macroscopic elongation of the samples. For example, H12 ABG PMA samples are elongated by 30% upon heating from room temperature to t 2 = 90°С [38]. It is noteworthy that the second phase tran sition in the samples (isotropization) occurs at the same critical size of columns in all compounds under study (Fig.…”
Section: Self Assembling Of Wedged Dendrons Based On Gallic Acid Derimentioning
confidence: 85%
“…This effect manifests itself in the signif icant macroscopic elongation of the samples. For example, H12 ABG PMA samples are elongated by 30% upon heating from room temperature to t 2 = 90°С [38]. It is noteworthy that the second phase tran sition in the samples (isotropization) occurs at the same critical size of columns in all compounds under study (Fig.…”
Section: Self Assembling Of Wedged Dendrons Based On Gallic Acid Derimentioning
confidence: 85%
“…X-ray analysis and optical microscopy [3,5] have shown that H12-ABG-4EO-PMA, H12-ABG-4EO-OH, and many of their homologues form columnar hexagonal (Col h ) phases. DSC heating scans for H12-ABG-4EO-PMA show two endotherms at~40 and~100 8C.…”
Section: Introductionmentioning
confidence: 99%
“…At the macroscopic level the potential benefits of well-defined dendritic structures are also clear. Some dendritic materials have been identified as nanoscopic host molecules (Hawker et al, 1993;Ottaviani et al, 1995;Newkome et al, 1991;Jansen et al, 1994), dendritic catalysts (Bhyrappa et al, 1996;Brunner, 1995), liquid crystals (Kwon et al, 1995;Ponomarenko et al, 1996), gene vectors (Kukowska-Latallo et al, 1996), contrast agents for magnetic resonance imaging (Wiener et al, 1994) and as tools for immunoassay (Tam, 1996;Singh et al, 1996). Since the early 1980s the main emphasis in dendrimer research has been on their synthesis Tomalia and Durst, 1990;Issberner et al, 1995;Newkome et al, 1996;Fréchet and Hawker, 1996;Zeng and Zimmerman, 1997;Matthews et al, 1998;Voit, 1995).…”
Section: Introductionmentioning
confidence: 99%